An Abaqus plugin for fatigue predictions. (January 2017) - Nesládek, M.; Španiel, M.
Highlights: The program provides a large number of prediction methods for material damage. Plain fatigue, creep and thermo-mechanical fatigue are covered. The solution can be obtained directly from the local Abaqus/CAE session. The solver engine can employ multiple CPU cores. Abstract: This paper presents the features and functions of a software tool called Fatigue Prediction Utility for Abaqus/CAE (FPU). It is designed as a plugin for the Abaqus commercial FE code allowing for fatigue predictions based on the results of Abaqus FE analyses. It also contains an interface for data transfer between Abaqus and PragTic, a standalone fatigue post-processor. The program contains a simple and intuitive graphical interface, which makes preparation of a fatigue analysis straightforward. The FPU fatigue solver may be executed on multiple CPU cores independently from Abaqus/CAE, which allows large-scale problems to be solved on server machines in reasonable time. An overview of the functionality of the plugin, available prediction models and the concept of data exchange between Abaqus and PragTic is given. Illustrative examples are given, where appropriate, in order to introduce features of the tool. Possible ways of adapting the code for interconnection with an FE solver other than Abaqus are discussed.